Proceedings of the 1st International Conference on Mobile Systems, Applications and Services 2003
DOI: 10.1145/1066116.1066127
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing mobility and network usage in a corporate wireless local-area network

Abstract: Wireless local-area networks are becoming increasingly popular. They are commonplace on university campuses and inside corporations, and they have started to appear in public areas [17]. It is thus becoming increasingly important to understand user mobility patterns and network usage characteristics on wireless networks. Such an understanding would guide the design of applications geared toward mobile environments (e.g., pervasive computing applications), would help improve simulation tools by providing a more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
314
1
5

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(333 citation statements)
references
References 14 publications
13
314
1
5
Order By: Relevance
“…One is representative of VANETs and is implemented in [10]. The second model is used to generate traces based on parameters derived by matching the TVCM model to the trace observed in [2]. We use the TVCM model to simulate the two traces just cited, and will call the traces MIT and VANET henceforth for the purpose of discussion.…”
Section: Mobility Of Nodesmentioning
confidence: 99%
“…One is representative of VANETs and is implemented in [10]. The second model is used to generate traces based on parameters derived by matching the TVCM model to the trace observed in [2]. We use the TVCM model to simulate the two traces just cited, and will call the traces MIT and VANET henceforth for the purpose of discussion.…”
Section: Mobility Of Nodesmentioning
confidence: 99%
“…Authors in the paper [1,2] paid more attention on user behavior in the wireless network, but these behavior studies served as parameters for network performance optimization. For example, authors in [1] pointed out the load of each access point was determined mostly by individual user behaviors.…”
Section: Related Workmentioning
confidence: 99%
“…For example, authors in [1] pointed out the load of each access point was determined mostly by individual user behaviors. In [2], it was found that the data-transfer rates of users follow a power law distribution. Power-law distributions were also found in certain characteristics of WWW, such as the distributions of document sizes and user requests for documents [5].…”
Section: Related Workmentioning
confidence: 99%
“…Previous analyses of public wireless networks in both academic and corporate environments [13,14], for example, have shown that users are often passive and network traffic is bursty. In these studies, wireless sessions were usually short-lived and the long-term connections that did exist were idle much of the time.…”
Section: Introductionmentioning
confidence: 99%